Penerapan Akuntansi Zakat sebagai Respon Administrasi Digital di Era Modern: Studi pada Badan Amil Zakat Nasional (BAZNAS) Provinsi Jawa Timur - Munir, Miftakhul; Rahmatillah Zidna, Rizka (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2021)
This study seeks to present ways or methods of applying accounting aspects in terms of controlling zakat administration, such as reports and institutional data. Administrative governance is an important thing to do, considering that zakat management requires valid, easy and clear data. Administrations such as finance, services, to reporting on institutional improvements require accounting to be more systematic and well-recorded. Because what has been a problem from the past until now, is the unification of the administration of zakat funds, it is still monotonous, rigid and manual. As a result, the required data is often not found. This has an impact on the effectiveness and development of the zakat institution itself. Therefore, by using a descriptive qualitative field study, this study will examine practically the application of zakat accounting for administrative regularity. The data collected comes from data about how zakat accounting works, hereinafter referred to as primary data. Primary data were collected through interview and documentation techniques with data analysis, reduction, editing and display. Data is only presented when it is final and there are no conflicts. From the research results, important things were found, namely 1) based on public accountants, PSAK No. 109, several policies made by BAZNAS East Java have not been realized. The reason for this problem is due to the ineffective management of zakat, infaq and shadaqah funds and the lack of adequate human resources in these business entities. 2) the method taken in completing it is to train and add quality human resources, especially in the accounting and finance departments. Then fix the information system at the accountant department.